Recreational-Geomorphological Zoning of the North-Eastern Caucasus - Zaburaeva Khava; Zaburaev Chingizkhan; Shaipova Aminat (Russian Journal of Earth Sciences)
The article presents the results of zoning of the territory of the North-Eastern Caucasus based on the analysis of geomorphological features and their influence on the organization of recreation. The following methods were used in this work: systematic, comparative-geographical and cartographic, as well as field studies and GIS-technologies. Map construction and statistical data processing were performed using ArcGis software package. The important role of relief in recreational specialization of the study area is shown. The features of methodological approaches to recreational assessments of relief in the works of domestic and foreign researchers are revealed. On the territory of the NorthEastern Caucasus on the basis of the analysis of qualitative and quantitative characteristics of relief taking into account the geological, paleogeographical and landscape features of the territory, five recreational-geomorphological districts were identified: plains, primorsky, foothills, intra-mountain and highland. In each of the indicated districts the tourism and recreational resources and prerequisites determining the development of certain types of tourist specialization are shown. In the plain recreational-geomorphologic district the most demanded are scientificcognitive, therapeutic, health-improving and ethno-cultural tourism. Alongside the historical and cultural heritage, the area has modern architecture, such as the Grozny-City high-rise building ensemble in the Chechen Republic. Primorsky district is favorably distinguished by opportunities for sea tourism. The foothill district is characterized by significant landscape diversity and the presence of recreational resources: fauna and flora, cultural and historical, etc. The most relevant types of tourism include: health-improving (terrenekur, forest therapy, phytotherapy, balneotherapy), sports (hunting, fishing, equestrian sports) and scientific-cognitive tourism. Intra-mountainous and highland areas are characterized by more complex contrasting relief, so the most relevant areas of tourism here include scientific-cognitive, geological, cultural-historical, sports and extreme tourism.